Essentials of corporate finance - Ross, Stephen A.; Westerfield, Randolph; Jordan, Bradford D. (New York McGraw-Hill Irwin, 2011)
The three basic themes that emerge in this student text are an emphasis on working at an intuitive level, a unified valuation approach to corporate finance and a managerial focus emphasising the role of the financial manager as a decision maker.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Corporations -- Finance